Isolated 'soft signs' of fetal choroid plexus cysts or echogenic intracardiac focus – consequences of their continued reporting. Issue 4 (11th October 2019) - Prentice, Grace; Welsh, Alec; Howat, Amy; Ross, Dominic; Henry, Amanda
Abstract: Background: Choroid plexus cysts (CPC) and echogenic intracardiac focus (EIF) are obsolete soft markers found on morphology ultrasound and not a valid reason for adjusting fetal risk of aneuploidy. Method: We conducted a retrospective audit of women referred to genetic counsellor and fetal medicine services at St George Hospital (SGH) and the Royal Hospital for Women (RHW) for CPC and EIF from 1 January 2006 to 31 December 2016 inclusive. Results: In total, 208 CPC and/or EIF referrals were identified, 118 (57%) of which were for isolated CPC and/or EIF and 102 (49%) occurring in women low risk for aneuploidy prior to morphology ultrasound. Significantly, more women had undergone combined first‐trimester screening in the 2014 to 2016 epoch vs. previous years at both SGH (P = 0.03) and RHW (P = 0.004). However, the number of women referred for CPC and EIF remained relatively constant. No fetus was born with a major structural or chromosomal abnormality in the group of low‐risk women with isolated signs. However, 18% of these women were referred to both genetic counselling and fetal medicine services, 7% had NIPT after morphology, 14% had amniocentesis, and 33% had additional ultrasound(s). Conclusion: Despite advances in screening technology, low‐risk women are still referred to specialist services for these 2 soft signs and undergoing unnecessary follow‐up, NIPT and amniocentesis.